Review of marine icing and anti-/de-icing systems. Issue 2 (3rd May 2016) - Rashid, Taimur; Khawaja, Hassan Abbas; Edvardsen, Kåre
ABSTRACT: The aim of this work is to review the phenomenon of icing in marine operations. The focus is on two main sources of icing, namely atmospheric and sea spray. The literature reveals that sea spray icing is the main contributor to marine icing. This work discusses the available ice accretion prediction models on ships and offshore structures. It also reviews the anti-/de-icing technologies that can be implemented on ships operating in cold climate regions. The significance of ice detection is acknowledged, and a brief review of various ice detection technologies is provided.